PJMHS 2022
DOI: 10.53350/pjmhs221641189
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Measles-Infected Pneumonia in Chilren and Infants

Abstract: Objective: Measles-related pneumonia in children and newborns is the primary goal of this research. Study Design: Cross-sectional Place and Duration: Conducted at BHU 399 GB Tandlianwala in duration of July 2021-Jan 2022. Methods: This research covered a total of 125 patients, including children and newborns of both sexes. Children under the age of seven were present. After receiving official permission from the authorities, the demographics, height, and weight of the patients were recorded. Those who had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Studies exposing the severity of measles in hospitalized youngsters provided substantial support for our findings. 33.66, 33, and 30.33 percent of infected children had mild, moderate, and severe measles infections, respectively [8][9] . In addition, it was observed that 32% had moderate infections and 24% had mild infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exposing the severity of measles in hospitalized youngsters provided substantial support for our findings. 33.66, 33, and 30.33 percent of infected children had mild, moderate, and severe measles infections, respectively [8][9] . In addition, it was observed that 32% had moderate infections and 24% had mild infections.…”
Section: Discussionmentioning
confidence: 99%
“…After literature screening, 50 articles published between 1996 and 2022 were retained for the systematic review. The studies were conducted in the following continents: 33 in Asia, 22,26,27,29,[31][32][33][35][36][37][38][39][40][41]43,45,[47][48][49][50][51][52][53][54][57][58][59][60][61][62][65][66][67] eight in Africa, 23,25,34,42,44,55,63,68 five in South America, 20,21,24,28,46 two in North America, 56,64 one in Central America, 19 and one in Oceania. 30 Four trials were conducted ...…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Phosphorus is the second major nutrient deficient in Egyptian soils. Phosphorus is of a great moment in photosynthesis, synthesis of nucleic acids, proteins, and lipids (Ayub et al, 2013;Khattab et al, 2019). Phosphorus displays a dogmatic role in legume seedling establishment its shoots and roots (Fathy, 2014).…”
Section: B)mentioning
confidence: 99%